Exosomal miRNA expression profiling in patients with imatinib resistant Chronic myeloid leukemia: A pilot study - Raphatphorn Navakanitworakul; Pirun Saelue; Tipparat Penglong; Piyatida Molika; Natakorn Nokchan; Natta Tansila; Hansuk Buncherd; Supinya Thanapongpichat; Kanitta Srinoun (PLoS ONE, 2025)
Chronic myeloid leukemia (CML) is a hematologic malignancy originating from hematopoietic stem cells and driven by the BCR-ABL fusion oncogene. Imatinib (IM), a tyrosine kinase inhibitor, is commonly used as a frontline therapy for CML. However, some patients exhibit primary resistance or show persistent molecular evidence of disease despite treatment. Emerging studies indicate that exosome-derived microRNAs (miRNAs) play a role in mediating drug resistance and may serve as promising biomarkers for cancer diagnosis and predicting therapeutic response. This study aimed to investigate the plasma exosomal miRNA expression profiles in CML patients to identify potential biomarkers associated with IM resistance. Exosomes were isolated from plasma samples of both IM-sensitive and IM-resistant CML patients. The exosomal miRNA content was analyzed using RNA sequencing, followed by differential expression analysis, which revealed 13 upregulated and 21 downregulated miRNAs in IM-resistant patients. Subsequent bioinformatics analysis indicated significant enrichment in pathways related to autophagy and PI3K-Akt signaling. Notably, miR-451a and miR-16–2-3p were among the most significantly upregulated miRNAs in exosomes from IM-resistant individuals. Interestingly, miR-16–2-3p expression showed a strong inverse correlation with clinical laboratory results, specifically blood urea nitrogen and creatinine levels. This pilot study identified plasma exosomal miRNAs, particularly miR-451a and miR-16–2-3p, as potential biomarkers for imatinib resistance in chronic myeloid leukemia. Target gene prediction was performed to explore their regulatory roles. Despite the limited sample size, these findings enhance our understanding of drug resistance mechanisms and warrant further validation in larger cohorts to assess their clinical relevance and therapeutic potential.